2017
DOI: 10.15389/agrobiology.2017.3.471eng
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Biological and Physical Parameters of Soils With Different Texture After Biochar Application

Abstract: A b s t r a c tMaintaining a favorable microbial and physical state of soils using new management practices is one of the key directions of sustainable land-use. Application of biochar (BC) is one of the new ways to improve soil quality and sustainability by increasing carbon sequestration and making significant changes in soil properties. Slow and fast pyrolysis is used to produce BC from different feedstock. Technological conditions of pyrolysis and feedstock type have key impacts on BC properties and its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Reduction in the amount of plant-available nitrogen in the unamended soil after BC slow application most likely is indicating immobilization of mineral N by C-rich material which is in line with our other work showing a decrease in the nitrification rates in a clayey loam soil after the biochars application (Buchkina et al, 2017). Based on the soil N 2 O fluxes which do not significantly change after BC slow application to the unamended soil, the lower NO 3 --N concentrations in the soil in this case cannot be attributed to denitrification losses of NO 3 --N being stimulated by the additional C (Clough et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Reduction in the amount of plant-available nitrogen in the unamended soil after BC slow application most likely is indicating immobilization of mineral N by C-rich material which is in line with our other work showing a decrease in the nitrification rates in a clayey loam soil after the biochars application (Buchkina et al, 2017). Based on the soil N 2 O fluxes which do not significantly change after BC slow application to the unamended soil, the lower NO 3 --N concentrations in the soil in this case cannot be attributed to denitrification losses of NO 3 --N being stimulated by the additional C (Clough et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Because of its high porosity and surface area, biochar alters the soil's physical properties such as bulk density [16,17], soil porosity [18], water-holding capacity [19,20], hydraulic conductivity [21], surface area, and penetration resistance [22]. Buchkina et al [23] and Castellini et al [24] have shown that biochar has the potential to change the root zone water balance of ecosystems. However, changes of soil chemical properties such as soil pH are more visible in soils with less suitable pH.…”
Section: Introductionmentioning
confidence: 99%
“…It turns out that application of biochar and biochar substrates or their combinations to soils could be a beneficial solution. Apparently, it is one of the new ways to improve soil quality and sustainability by increasing the soil carbon content and making significant changes in soil properties (Buchkina et al, 2017). Investing in biochar that is applied to soil is a long-term matter that may discourage farmers from using it.…”
Section: Introductionmentioning
confidence: 99%